Analytic functions, Subordination, q-Ruscheweyh derivative, Hadamard product, Univalent function - Kassar, Osamah N.; Juma, Abdul Rahman S. (Iraqi Journal of Science, 2020)
In this paper, making use of the q-R uscheweyh differential operator , and the notion of t h e J anowski f unction, we study some subclasses of holomorphic f- unction s . Moreover , we obtain so me geometric characterization like co efficient es timat es , rad ii of starlikeness ,distortion theorem , close- t o- convexity , con vexity, ext reme point s, neighborhoods, and the i nte gral mean inequalities of func tions affiliation to these c lasses